Harnessing microRNA-enriched extracellular vesicles for liquid biopsy - Ko, Song Yi; Lee, WonJae; Naora, Honami (Frontiers in Molecular Biosciences, 2024)
Extracellular microRNAs (miRNAs) can be detected in body fluids and hold great potential as cancer biomarkers. Extracellular miRNAs are protected from degradation by binding various proteins and through their packaging into extracellular vesicles (EVs). There is evidence that the diagnostic performance of cancer-associated extracellular miRNAs can be improved by assaying EV-miRNA instead of total cell-free miRNA, but several challenges have hampered the advancement of EV-miRNA in liquid biopsy. Because almost all types of cells release EVs, cancer cell-derived EVs might constitute only a minor fraction of EVs in body fluids of cancer patients with low volume disease. Furthermore, a given cell type can release several subpopulations of EVs that vary in their cargo, and there is evidence that the majority of EVs contain low copy numbers of miRNAs. In this mini-review, we discuss the potential of several candidate EV membrane proteins such as CD147 to define cancer cell-derived EVs, and approaches by which subpopulations of miRNA-rich EVs in body fluids might be identified. By integrating these insights, we discuss strategies by which EVs that are both cancer cell-derived and miRNA-rich could be isolated to enhance the diagnostic performance of extracellular miRNAs.